PENGARUH LIABILITAS JANGKA PENDEK DAN LIABILITAS JANGKA PANJANG TERHADAP PROFITABILITAS PT. MINERAL SUMBERDAYA MANDIRI Tbk. - Nurhaslindah, nurhaslindah (Program Studi Akuntansi Lembaga Keuangan Syariah, FEBI, IAIN Parepare, 2025)
This study aims to analyze and examine the effect of short-term liabilities and long-term liabilities on profitability at PT. Mineral Sumberdaya Mandiri Tbk during the 2020–2023 period. The research employs a quantitative approach using multiple linear regression analysis to determine the extent to which both types of liabilities influence the company’s ability to generate profits. The data used are secondary data obtained from the company’s annual financial statements published through the Indonesia Stock Exchange (IDX). The results reveal that, partially, short-term liabilities have no significant effect on profitability, with a significance value of 0.212, which is greater than 0.05. Conversely, long-term liabilities have a significant effect on profitability, with a significance value of 0.033, which is less than 0.05. Simultaneously, both independent variables significantly affect profitability, as indicated by an F-statistic value of 882.377, which exceeds the F-table value of 19.00, with a significance level of 0.024. The Adjusted R Square value of 0.998 indicates that 99.8% of the variation in profitability can be explained by changes in short-term and long-term liabilities, while the remaining 0.2% is influenced by other factors outside the model. These findings confirm that efficient management of the capital structure, particularly long-term liabilities, plays a crucial role in improving financial performance and profitability within the mining sector.